Stress Analysis of SIC Reinforced Polyester Nano Composite Spur Gear - Selvam, R.; Ravi, S.; Balasubramanian, K. (International Journal of Engineering and Technology, 2018)
Gears are most powerful machine element to transmit the motion between rotating shaft. It acts as a dominating transmission system from many years ago. In this study, we analyzed a spur gear machine toolfor special application Â using theoretical method and Finite element analysis. Here, the bending stress on the spur gear is analyzed since these stresses induced play a vital role in gear life. The analysis presented the effect of gear material on induced bending stress. Finally results of theoretical method and Finite element analysis were determined and when compared gives a better results.Â Â